1982
DOI: 10.1103/physrevb.26.5904
|View full text |Cite
|
Sign up to set email alerts
|

Soft-mode spectroscopy in cubic BaTiO3by hyper-Raman scattering

Abstract: Hyper-Raman scattering from cubic BaTi03 is studied to clarify the controversies about the low-frequency dielectric response in this material. Applying the Auctuation-dissipation theorem, we obtain the imaginary part e"(0) of the dielectric function in the wave-number range from 3 to 150 cm '. e"(0) can be adequately described by a classical singleoscillator dispersion formula. In approaching the Curie temperature, we find a continuous decrease of the mode frequency 00. The relative damping constant y/Qo excee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
1
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(70 citation statements)
references
References 21 publications
5
63
1
1
Order By: Relevance
“…As measured by HyperRaman spectroscopy [5,6], a relaxational dynamics was also observed in the paraelectric BaTiO 3 near T c . NMR experiment [7] has recently shown that Ti ion in the paraelectric phase of BaTiO 3 flutters among off-center sites, claiming the coexistence of order-disorder and displacive characters in phase transition of BaTiO 3 as that predicted by simulation [8].…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…As measured by HyperRaman spectroscopy [5,6], a relaxational dynamics was also observed in the paraelectric BaTiO 3 near T c . NMR experiment [7] has recently shown that Ti ion in the paraelectric phase of BaTiO 3 flutters among off-center sites, claiming the coexistence of order-disorder and displacive characters in phase transition of BaTiO 3 as that predicted by simulation [8].…”
mentioning
confidence: 80%
“…The cluster is a dynamic correlated region where unit cells polarize coherently. NMR experiment [7] showed a relaxation time of Ti ion at each off-center site to be about 10 ns at a temperature of 5 C. On the other hand, hyper-Raman experiment [5] showed the relaxation time of the overdamped phonon to be an order of several hundreds of picoseconds in the same temperature region. Thus, an order of nanoseconds might be a measure of the relaxation time of cluster.…”
Section: Volume 93 Number 8 P H Y S I C a L R E V I E W L E T T E R mentioning
confidence: 99%
See 1 more Smart Citation
“…It saturates at ω T O1 ≈ 31 cm −1 upon approaching T C = 403 K. 19 According to the displacive model of the phase transition, it is this (soft) mode that is responsible for the ferroelectric instability in BaTiO 3 . 42,43 On the other hand, the Last (ω T O2 ≈ 180 cm −1 ) and the Axe (ω T O4 ≈ 498 cm −1 ) modes are nearly T -independent in a wide temperature range.…”
Section: Optical Conductivitymentioning
confidence: 99%
“…15 In fact, disorder in the form of microscopic clusters of orthorhombic Ti off-center displacements exists already in rhombohedral phase as revealed by Mn 4+ electron paramagnetic resonance (EPR). 16,17 Evidence of both order-disorder and displacive character of the phase transitions in BaTiO 3 has been found by variety of techniques including nuclear magnetic resonance 18 (NMR), extended x-ray-absorption fine structure (EX-AFS), x-ray-absorption near-edge structure 15 (XANES), Raman 19 and IR 20 spectroscopy. It becomes obvious, therefore, that both resonant (optical phonons) and nonresonant (relaxation) modes have to be considered in the problem of electron-lattice interaction in BaTiO 3 .…”
Section: Introductionmentioning
confidence: 99%